The Effect of Dividend Policy on Share Price Volatility in Indonesia - Utami, Entri Lutfi; Wtiastuti, Rini Setyo (Management Analysis Journal, 2019)
This study aimed to determine the effect of dividend policy on stock price volatility in Indonesia. Indicators dividend policy is a dividend payout ratio and dividend yield. The analysis in this study also involves other factors suspected to affect the stock price volatility, such as company size, company earnings volatility, debt level, and the rate of growth of the company. The population in this study are all companies listed in Indonesia Stock Exchange in 2013-3017. The samples in the study using purposive sampling method. The research sample of 270 units of observational data. The analytical method used is multiple regression analysis using Eviews program 9. The results showed that the variables that have a significant influence on the volatility of the stock price is just dividend yield. The higher the dividend yield, the lower the volatility of the stock price. Control variables significant negative effect of firm size and debt level positf significant effect. For further research should add other variables such as macroeconomic variables such as inflation, as well as extending the period of study.